PRINCIPALS’ ADMINISTRATIVE PROCESS STRATEGIES FOR THE ACHIEVEMENT OF QUALITY ASSURANCE IN SECONDARY SCHOOLS IN IKOM EDUCATION ZONE OF CROSS RIVER STATE - Ekpung, Akata, Charles; Ebam, Ndep, Tiku (Journal of Geography, Regional Planning and Development, 2025)
Objective: This study examined principals’ administrative process strategies for the achievement of quality assurance in secondary schools in Ikom education zone of Cross River State. Specifically, the study was to examine principals’ planning strategies, organizing strategies, and principals’ coordinating strategies for the achievement of quality assurance in secondary schools in Ikom Education Zone of Cross River State. Method: The study adopted descriptive survey research design. The population of the study comprised 129 principals of the 129 public secondary schools. The entire population was used. The instrument was of Principals’ Quality Assurance Strategies Questionnaire (PQASQ) with reliability coefficient of 0.76 was used for data collection. Mean and standard deviation were used to answer the research questions. Independent t- test was used to test the hypotheses at 0.05 level of significance. Results: The result showed that principals’ administrative strategies do significantly impact on quality assurance of secondary schools in the areas of enhancing instructions and promoting school plants management, provision of instructional materials, encouraging job training and staff development, promoting sports and psychomotor domains, and supporting financial management and accountability. Novelty: Based on the findings of the study, it was recommended among others that principals should be adequately enlightened with more robust administrative strategies through seminars and conferences which may include classroom observation, analysis/strategy, post observation conferences and post conferences analysis and that Ministries of Education should make it mandatory for all school heads to be involved in quality assurance in order to assess teachers’ job outputs as well as students’ academic performance.